The Use of Learning Media in Increasing Children's Interest in Learning at Nurul Haq Private Elementary School - Laatifah, Yuli (MANDAILING GLOBAL EDUKASIA, 2025)
The problem raised in this PTK is that more than 40% of students get low scores (below KKM) in the Aqidah Akhlak KD 3.1 lesson. The meaning and provisions for the application of gratitude used are using ordinary media. The action is planned with 2 cycles, each cycle consisting of 1 meeting, each meeting consisting of preliminary activities, core activities and closing activities. This PTK is equipped with theories and research methods accompanied by the required instruments. The theory presented concerns the problem of Gratitude. The method used is a qualitative research method. This report is equipped with observation instruments concerning student behavior in the learning process and observation instruments for teachers, both observations of learning plans and actions in the learning process. After the action was carried out from 2 cycles and 2 meetings, data was found which was the result of observer observations. After the data was discussed/analyzed, it was concluded that the use of Learning Media can increase student interest. Furthermore, the author submits the following recommendations: ordinary learning media must be replaced with IT learning media that is appropriate in the teaching and learning process of the Aqidah Akhlak subject, especially in the material of Gratitude.